Aplikasi Pemanfaatan Sarang Lebah untuk Mempercepat Pertumbuhan Ikan Nila (Oreochromis niloticus) - Fabian Ardianta (Jurnal Airaha, 2012)
. Tilapia is one of economically freshwater commodity developed in indonesia due to it´s good taste,fast growth and commonly cultured by farmers .This research was conducted to evaluate the application of bee´s nest to growth of tilapia.Bee´s nest was mixed with pellet and applied to tilapia´s frys.Mixed pellet was given ince a day and frys measured weekly.After six week of treatment,mixen pellet showed faster grosth both for body lenght and body weinght 0,1 cm range for body length and 0,4 gram range for body weight compared to non-mixed pellet.